2020
DOI: 10.22226/2410-3535-2020-1-43-47
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aluminum nitride nanoparticles on the structure, phase composition and properties of materials of the Ti-B-Fe system obtained by SHS-extrusion

Abstract: The SHS-extrusion method, which combines the combustion processes in the mode of self-propagating high-temperature synthesis (SHS) and the subsequent high temperature shear deformation of the combustion products, was used to obtain metal-ceramic composite materials based on titanium boride with an iron matrix modified by additives of nanoaluminum nitride of grade SHS-Az. It was shown that small additions of nanoscale aluminum nitride powder (3 and 5 wt.%) to the initial mixture of the Ti-B-Fe system had a sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Since metal-cutting tools are predominantly made of alloy steel, iron is used as a metal binder. The authors [51] compared the structure and properties of SHS electrode materials based on titanium borides obtained by SHS extrusion, in which iron acted as a metal binder, and the same materials modified with aluminum nitride nanoparticles. For the composition without any modifier, it was found that the SHS electrode materials consisted of grains of titanium diboride located in the intermetallic TiFe matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Since metal-cutting tools are predominantly made of alloy steel, iron is used as a metal binder. The authors [51] compared the structure and properties of SHS electrode materials based on titanium borides obtained by SHS extrusion, in which iron acted as a metal binder, and the same materials modified with aluminum nitride nanoparticles. For the composition without any modifier, it was found that the SHS electrode materials consisted of grains of titanium diboride located in the intermetallic TiFe matrix.…”
Section: Introductionmentioning
confidence: 99%